The Influence of Euphemism and Dysphemism on Politeness in the Malay Dialect of Kampar - Morelent, Yetty; Irawan, Bambang (KnE Social Sciences, 2022)
This research aimed to describe the form and function of euphemisms and dysphemisms and their influence on politeness in the Kampar community. This was qualitative research and descriptive methods were used. Participants were native Riau Malay speakers of the Kampar dialect in Kampung Panjang village. The results of this research indicated that euphemism and dysphemism in the Riau Malay Kampar dialect are spoken in the form of words, phrases, and expressions. Dysphemism is more widely used than euphemism. This is due to the low level of education and knowledge about politeness, poor social relations with speech partners, and intimacy and psychological closeness in socializing that make them tend to use such abusive language. It was found in this study that euphemisms function as a means of refining speech, avoiding taboo, and hiding the truth. The functions of dysphemism are expressions of anger, criticism, insinuation, insult and to express taboo or vulgar things. Keywords: Eufemism And Dysphemism, Language Politeness